Assessing health-related quality-of-life in individuals with haemophilia. - Miners, A; Sabin, C; Tolley, K; Jenkinson, C; Kind, P; Lee, C (1999)
The objectives of this study were to analyse current levels of health-related quality-of-life (HR-QoL) in individuals with severe haemophilia and to assess the scope for these levels to improve. To do this, 249 individuals with severe, moderate and mild haemophilia were asked to complete Medical Outcomes Study (MOS) Short-Form 36 (SF-36) and EuroQol (EQ-5D) questionnaires. Access was also gained to two appropriate normative data sets. The results from these questionnaires showed that HIV status, history of orthopaedic surgery and bleeding frequency in the previous calendar year were not strong predictors of HR-QoL for individuals with severe haemophilia. However, for the majority of scales, age was found to be a strong predictor of HR-QoL for this patient group. The results from the analysis also showed that compared to individuals with moderate/mild haemophilia and the UK male normative population, individuals with severe haemophilia generally recorded poorer levels of HR-QoL. These results suggest, therefore, that individuals with severe haemophilia have reduced levels of HR-QoL compared to individuals with moderate/mild haemophilia and the general population, irrespective of differences in age. The results also suggest that the scope for primary prophylaxis to increase HR-QoL in individuals with severe haemophilia is significant.